2013
DOI: 10.1152/ajpendo.00434.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the green tea polyphenol epigallocatechin-3-gallate on high-fat diet-induced insulin resistance and endothelial dysfunction

Abstract: Insulin resistance, a hallmark of metabolic disorders, is a risk factor for diabetes and cardiovascular disease. Impairment of insulin responsiveness in vascular endothelium contributes to insulin resistance. The reciprocal relationship between insulin resistance and endothelial dysfunction augments the pathophysiology of metabolism and cardiovascular functions. The most abundant green tea polyphenol, epigallocatechin-3-gallate (EGCG), has been shown to have vasodilator action in vessels by activation of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 81 publications
0
61
0
Order By: Relevance
“…Recent studies have shown a strong correlation between the consumption of green tea and the prevention of NAFLD. Other studies have shown that EGCG reduced the severity of liver injury by reducing circulating insulin, improving insulin sensitivity and attenuating insulin resistance in type 2 diabetes mellitus (T2DM) or NAFLD mice [12][13][14] . Although EGCG reduces circulating insulin, it is not clear whether IDE is involved.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown a strong correlation between the consumption of green tea and the prevention of NAFLD. Other studies have shown that EGCG reduced the severity of liver injury by reducing circulating insulin, improving insulin sensitivity and attenuating insulin resistance in type 2 diabetes mellitus (T2DM) or NAFLD mice [12][13][14] . Although EGCG reduces circulating insulin, it is not clear whether IDE is involved.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia may be caused by lipid metabolism dysfunction (Jang et al, 2013, Ezhumalai et al, 2014. The hypertriglyceridemia observed in ACG was not the result of AOM-induced hyperglycemia, because the plasma glucose concentration in COG was similar to the ACG, however plasma triglyceride concentration in the COG was significantly lower than that in ACG.…”
Section: Discussionmentioning
confidence: 86%
“…Our study use the combination the streptozotocin and high fat diet (40%) fat to maintain the hyperglycemic state. Previous report suggested that HFD administration induce insulin resistance via PKC activation by high level free fatty acid that consequently interfered IRS activation (Jang, 2013). Moreover, our study used the combination of animal fat and hydrogenated fat to maintain insulin resistance.…”
Section: Development Of Hyperglycemiamentioning
confidence: 91%